PERKEMBANGAN SISTEM PEMBAYARAN DI INDONESIA - Vera Intanie Dewi (Bina Ekonomi, 2006)
A payment system is a set of contractual arrangements, operating facilities and technical mechanism used for presentation, authentication, and acceptance of payment orders, and discharge of the resultant financial obligation through the exchange of value between individuals, banks and other entities domestically and cross - border. An efficient, fast, secure and reliable payment system is the most important factor in creating a healthy banking system, which in turn will support economic activities. The development of payment system is different in every country. It depends on the economic system and financial system in that particular country. In Indonesia, Bank Indonesia continually develops the national payment system in order to have a comprehensive and integrated payment system, which is effective, efficient, safe, reliable and bears low risk. Thus, Bank Indonesia is expected to fulfill public needs of transaction, whether small or large transaction, using different method of payments, such as electronic-based method, cards, papers, notes and others.